The Impact of Agency Banking on Financial Performance of Listed Deposit Money Banks in Nigeria - Olalere Victor Dotun; Anthony Kolade Adesugba (HM Journals, 2022)
The study examined the impact of agency banking on the financial performance of listed deposit money banks in Nigeria for the period 2011-2020. The sample size of the study is 12 DMBs. Secondary data extracted from the financial reports and accounts of the DMBs that prepared the study sample were used. The study employed Random Effect as the best estimator of the regression model. One of the findings revealed volume of accounts opened by agent has significant positive impact on the financial performance of DMBs in Nigeria. Also, the study concluded that volume of electronic transfers positively increases banks financial performance. The study recommends that DMBs agent should encourage people to open accounts and carry out transaction with the accounts since account open by agent was found being among the factors that increase DMBs profitability. In addition, DMBs should put in place incentive that would encourage customers to reduce their level of withdrawals by giving out reward to customers that has not make withdraw for some period of time. Also, Regulators should increase the interest rate for customers saving which would encourage customer not to make withdraw frequently.